Essential role for the histone acetyltransferase KAT7 in T cell development, fitness, and survival. Issue 4 (12th October 2016) - Newman, Dane M; Voss, Anne K; Thomas, Tim; Allan, Rhys S
Abstract : Data in support of a role for KAT7 in T cell development. Abstract: Histone acetylation has an important role in gene regulation, DNA replication, and repair. Because these processes are central to the development of the immune system, we investigated the role of a previously unstudied histone acetyltransferase named KAT7 (also known as Myst2 or HBO1) in the regulation of thymopoiesis and observed a critical role in the regulation of conventional and innate-like T cell development. We found that KAT7-deficient thymocytes displayed normal, positive selection and development into mature single-positive αβ thymocytes; however, we observed few peripheral CD4 + or CD8 + T cells. The observed effects did not appear to arise from alterations to DNA replication, the TCR repertoire, or a block in thymocyte maturation and, more likely, was linked to survival defects related to gene deregulation because KAT7 deficiency led to an almost complete and specific loss of global histone-H3 lysine 14 acetylation (H3K14ac). Overall, we demonstrated a nonredundant role for KAT7 in the maintenance of H3K14ac, which is intimately linked with the ability to develop a normal immune system.